Dynamics of international aid in the Chinese context: a case study of the World Bank's Cixi Wetlands Project in Zhejiang Province - Tan-Mullins, May; Chen Guangli, Gary (Cambridge University Press, 2012)
Environmental degradation in China, intensified by open-door reforms and industrialization, has been increasing at an alarming scale. Domestically, environmental governance has been poor, often due to institutional constraints and lack of “good practices.” However, recently there have been studies on how the “foreign factor” might have profound positive effects on capacity building in China and how international actors could lead to the successful introduction of good environmental governance. In this article, we present a study of a successful case: the World Bank Global Environmental Facility Cixi Wetlands project in Ningbo, China. The article examines the following: (a) the unique local context enabling the diffusion of international norms; (b) the factors which contribute to the World Bank's leverage role in restructuring local project governance; and (c) the changes in local environmental governance arising from the Bank's involvement. By evaluating this project, the article will demonstrate how the World Bank managed to introduce and socialize local actors into project-specific policy dialogues and procedures that enhanced local compliance with its international practices and standards.